2017
DOI: 10.1074/jbc.m117.797696
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial meta-cleavage hydrolase LigY belongs to the amidohydrolase superfamily, not to the α/β-hydrolase superfamily

Abstract: Strain SYK-6 of the bacterium sp. catabolizes lignin-derived biphenyl via a-cleavage pathway. In this pathway, LigY is proposed to catalyze the hydrolysis of the -cleavage product (MCP) 4,11-dicarboxy-8-hydroxy-9-methoxy-2-hydroxy-6-oxo-6-phenyl-hexa-2,4-dienoate. Here, we validated this reaction by identifying 5-carboxyvanillate and 4-carboxy-2-hydroxypenta-2,4-dienoate as the products and determined the and / values as 9.3 ± 0.6 s and 2.5 ± 0.2 × 10 m s, respectively. Sequence analyses and a 1.9 Å resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 57 publications
4
37
0
Order By: Relevance
“…In addition to the catabolic pathways, a large number of detailed biochemical studies and structural analyses on catabolic enzymes, including ring‐cleavage extradiol dioxygenases, protocatechuate 4,5‐cleavage pathway enzymes and hydrolase and decarboxylase involved in biphenyl catabolism, were performed (Hobbs et al ., ; Barry and Taylor, ; Sugimoto et al ., ; Barry et al ., ; Zhang et al ., ; Vladimirova et al ., ; Kuatsjah et al ., ). Here, we cover two topics regarding ring‐cleavage extradiol dioxygenase.…”
Section: Overview Of Updated Lignin‐derived Aromatic Catabolic Pathwamentioning
confidence: 97%
“…In addition to the catabolic pathways, a large number of detailed biochemical studies and structural analyses on catabolic enzymes, including ring‐cleavage extradiol dioxygenases, protocatechuate 4,5‐cleavage pathway enzymes and hydrolase and decarboxylase involved in biphenyl catabolism, were performed (Hobbs et al ., ; Barry and Taylor, ; Sugimoto et al ., ; Barry et al ., ; Zhang et al ., ; Vladimirova et al ., ; Kuatsjah et al ., ). Here, we cover two topics regarding ring‐cleavage extradiol dioxygenase.…”
Section: Overview Of Updated Lignin‐derived Aromatic Catabolic Pathwamentioning
confidence: 97%
“…5 Only recent evidence of its occurrence in the 5,5'dehydrodivanillate (DDVA) pathway had been reported. 6,7 The first study 6 reported an enzymatic production of this compound from its aldol product precursor, 4-hydroxy-4methyl-2-oxoglutaric acid (HMOG), with analysis by HPLC but without verification with an authentic analytical standard. The more recent work 7 also reported evidence of CHPD based on the enzymatic fragmentation of an upstream lignin derived aromatic compound that lead to the suspected CHPD and 5-carboxyvanillate.…”
Section: Introductionmentioning
confidence: 99%
“…BphD is a serine‐dependent member of the α/β‐hydrolase superfamily, typical of all but one of the MCP hydrolases characterized to date. The only MCP hydrolase that differs is LigY, which is a Zn 2+ ‐dependent member of the amidohydrolase superfamily . It is unclear how these two enzymes use such different catalytic machinery to catalyze similar reactions.…”
Section: Introductionmentioning
confidence: 99%